Analysis of the constitutional court's decision on the age limit of presidential and vice-presidential candidates in the perspective of Rechtstaat - Hendra Agu Ate (Dynamics of Politics and Democracy, 2024)
Purpose: This study aims to analyze the Constitutional Court Decision Number 90/PUU-XXI/2023 on the age limit for presidential and vice-presidential candidates from the perspective of Rechtsstaat and the principle of Trias Politica, emphasizing the rule of law and the balance of power in a democratic legal state.. Research methodology: The research employs a normative legal approach using a conceptual and statutory approach. It analyzes constitutional provisions, legal theories, and judicial decisions to evaluate the decision's alignment with the principles of the rule of law and separation of powers. Results: The findings reveal that the Constitutional Court’s partial granting of the petition on the age requirement reflects potential political influence, thereby raising questions regarding judicial neutrality and deviation from Trias Politica. The Court’s justification as an “open legal policy” illustrates a blurred line between judicial interpretation and legislative authority, which undermines the Rechtsstaat ideal that demands strict legal consistency and institutional balance. Conclusions: The decision highlights a deviation from the principles of a legal state (Rechtsstaat) and Trias Politica, as the judiciary may have overstepped its role, thereby affecting public trust and the integrity of the rule of law. Limitations: This study is limited to doctrinal analysis and does not include empirical assessment of political impacts or public perception. Contribution: The research contributes to scholarly discourse on the intersection of law and politics in Indonesia, offering a critical evaluation of judicial behavior within the framework of constitutional democracy.